2016
DOI: 10.1039/c6ra10731a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the synthesis of vinyl sulfones

Abstract: Development of methodology for the preparation of vinyl sulfones is of significant interest to organic chemists. Recently, numerous useful methods have been developed, mainly including direct sulfonylation of olefins and alkynes, decarboxylative sulfonylation of α,β-unsaturated carboxylic acids and decomposition of tosylhydrazones. This review will focus on recent achievements in vinyl sulfones synthesis and the mechanisms of the reactions are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
64
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(64 citation statements)
references
References 113 publications
0
64
0
Order By: Relevance
“…Vinyl sulfones, on the other hand, are among the most electron deficient/reactive alkenes and have been widely used as partners in ionic, radical additions and cycloadditions, or in the total synthesis of natural products (Scheme a) . Their importance is underlined by a recent literature review that stated that over 42 new syntheses of vinyl sulfones have been reported in the last five years alone . Given fluorine's pre‐eminence in medicinal chemistry and the sulfonyl group's importance as an organic building block, their juxtaposition on a vinyl or carbonyl template (fluoro‐ A or fluoro ‐B in Scheme ) should lead to desirable motifs in medicinal or synthetic chemistry but their syntheses are quite challenging.…”
Section: Methodsmentioning
confidence: 99%
“…Vinyl sulfones, on the other hand, are among the most electron deficient/reactive alkenes and have been widely used as partners in ionic, radical additions and cycloadditions, or in the total synthesis of natural products (Scheme a) . Their importance is underlined by a recent literature review that stated that over 42 new syntheses of vinyl sulfones have been reported in the last five years alone . Given fluorine's pre‐eminence in medicinal chemistry and the sulfonyl group's importance as an organic building block, their juxtaposition on a vinyl or carbonyl template (fluoro‐ A or fluoro ‐B in Scheme ) should lead to desirable motifs in medicinal or synthetic chemistry but their syntheses are quite challenging.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Notably, the generation of a sulfonyl radical and its addition to unsaturated CÀC bonds (such as alkenes and alkynes) contribute much to recent advances in the synthesis of sulfones. [6,7] The single-electron oxidation of sulfinates [8] or sulfinic acids [9] and the oxidative cleavage of sulfonyl hydrazides [10] also provide efficient routes for the formation of sulfonyl radicals (Scheme 1 b). [5,6] For instance, sulfonyl radicals can be produced from their corresponding sulfonyl halides, sulfonyl selenides, sulfonyl azides, and sulfonyl cyanides in the presence of radical initiators, light, or catalysts (Scheme 1 a).…”
mentioning
confidence: 99%
“…[5,6] For instance, sulfonyl radicals can be produced from their corresponding sulfonyl halides, sulfonyl selenides, sulfonyl azides, and sulfonyl cyanides in the presence of radical initiators, light, or catalysts (Scheme 1 a). [6,7] The single-electron oxidation of sulfinates [8] or sulfinic acids [9] and the oxidative cleavage of sulfonyl hydrazides [10] also provide efficient routes for the formation of sulfonyl radicals (Scheme 1 b). The addition of these generated sulfonyl radicals to alkenes or alkynes usually leads to various sulfonated products by different radical trapping processes.…”
mentioning
confidence: 99%
“…The development of synthetic approaches to vinyl sulfones has received substantial attention in recent years. [5,6] Nevertheless, the synthesis of a-substituted vinyl sulfones, which have great potential application in biological sciences, [7] still remains an outstanding challenge. [5,6] Nevertheless, the synthesis of a-substituted vinyl sulfones, which have great potential application in biological sciences, [7] still remains an outstanding challenge.…”
mentioning
confidence: 99%
“…Firstly, eosin Y, widely used as a photoredox catalyst due to its low cost and simple purification, [10] was tested. Intriguingly, when the reaction was performed with K 2 CO 3 as base, the Markovnikov product was exclusively obtained in 86 % yield (Table S1, a considerable influence on the efficiency of this transformation (Table S1, entries [5][6][7][8][9][10]. Encouraged by the result, various bases, reacting with sulfinic acids to form sulfinate salts, were next investigated.…”
mentioning
confidence: 99%